2021
DOI: 10.1111/febs.16297
|View full text |Cite
|
Sign up to set email alerts
|

Akt acts as a switch for GPCR transactivation of the TGF‐β receptor type 1

Abstract: Transforming growth factor (TGF)‐β signalling commences with the engagement of TGF‐β ligand to cell surface TGF‐β receptors (TGFBR) stimulating Smad2 carboxyl‐terminal phosphorylation (phospho‐Smad2C) and downstream biological responses. In several cell models, G protein‐coupled receptors (GPCRs) transactivate the TGF‐β receptors type‐1 (TGFBR1) leading to phospho‐Smad2C, however, we have recently published that in keratinocytes thrombin did not transactivate the TGFBR1. The bulk of TGFBRs reside in the cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…Moreover, the inhibition of this pathway induced by ASP can be reversed by inhibiting ASP-triggered mitochondrial fission, suggesting that the ASPtriggered mitochondrial fission is at least an important factor for endothelial dysfunction. This is well supported by another finding that the phosphorylation of the serine 473 site in AKT can be directly modulated by GPCR-mediated signaling and that the activation of AKT is critical for the activity of DRP1 [35][36][37]. Therefore, our current data provide new insights on how ASP affects the fission of mitochondria.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the inhibition of this pathway induced by ASP can be reversed by inhibiting ASP-triggered mitochondrial fission, suggesting that the ASPtriggered mitochondrial fission is at least an important factor for endothelial dysfunction. This is well supported by another finding that the phosphorylation of the serine 473 site in AKT can be directly modulated by GPCR-mediated signaling and that the activation of AKT is critical for the activity of DRP1 [35][36][37]. Therefore, our current data provide new insights on how ASP affects the fission of mitochondria.…”
Section: Discussionsupporting
confidence: 83%
“…These pathways are closely related to the therapeutic mechanism of TPP@(CeO 2 +ROF), particularly the GPCR signaling pathway, which represents an important target for drug action that is closely related to glial cell development and inflammatory response . Furthermore, gene set enrichment analysis (Figure E–H) indicated that treatment with TPP@(CeO 2 +ROF) was associated with the downregulation of TGF-β signaling pathway-mediated inflammation levels and promotion of neurodevelopment through the GPCR signaling pathway . This is consistent with the immunofluorescence staining results at the in vivo level.…”
Section: Results and Discussionsupporting
confidence: 82%
“…30 Furthermore, gene set enrichment analysis (Figure 9E−H) indicated that treatment with TPP@(CeO 2 +ROF) was associated with the downregulation of TGF-β signaling pathway-mediated inflammation levels and promotion of neurodevelopment through the GPCR signaling pathway. 58 This is consistent with the immunofluorescence staining results at the in vivo level. Moreover, Wiki data analysis showed that TPP@(CeO 2 +ROF) mediated the brain-derived neurotrophic factor and TNF-α signaling pathways to exert potent neuroprotective effects.…”
Section: P R E P a R A T I O N A N D C H A R A C T E R I Z A T I O N ...supporting
confidence: 90%
“…The activation of the latent TGF-β is achieved through various mechanisms, involving integrins, proteases and reactive oxygen species (ROS) [15,16]. Our group identified that G protein-coupled receptors (GPCR) such as thrombin [17][18][19][20], endothelin [21,22] and lysophosphatidic acid [23,24] via specific biochemical mechanisms could transactivate the TGFBR1 leading to the phosphorylation of Smad2. Transactivation-dependent signalling involves cell surface receptor transactivation of a second cell surface receptor occurring in the absence of transcription and translation of intermediate products [25,26].…”
Section: Introductionmentioning
confidence: 99%